(untitled) (TAJ: Journal of Teachers Association, 2019)
Interstitial lung disease is rare diseases in children. Respiratory symptoms appear progressively, are often subtle and diagnosis is often delayed by many months after onset. The histological diagnosis is confirmatory but high-resolution chest computed tomography is the most sensitive imaging technique for demonstrating and identifying interstitial lung disease. Interstitial lung disease in children mostly is idiopathic though it may be caused by several conditions. TAJ 2018; 31(2): 73-79